Relevance and efficacy of breast cancer screening in BRCA1 and BRCA2 mutation carriers above 60 years: A national cohort study. Issue 12 (20th May 2014) - Saadatmand, Sepideh; Vos, Janet R.; Hooning, Maartje J.; Oosterwijk, Jan C.; Koppert, Linetta B.; de Bock, Geertruida H.; Ausems, Margreet G.; van Asperen, Christi J.; Aalfs, Cora M.; Gómez Garcia, Encarna B.; Meijers‐Heijboer, Hanne; Hoogerbrugge, Nicoline; et al.
<x xml:space="preserve">Abstract</x> Annual MRI and mammography is recommended for BRCA1/2 mutation carriers to reduce breast cancer mortality. Less intensive screening is advised ≥60 years, although effectiveness is unknown. We identified BRCA1/2 mutation carriers without bilateral mastectomy before age 60 to determine for whom screening ≥60 is relevant, in the Rotterdam Family Cancer Clinic and HEBON: a nationwide prospective cohort study. Furthermore, we compared tumour stage at breast cancer diagnosis between different screening strategies in BRCA1/2 mutation carriers ≥60. Tumours >2 cm, positive lymph nodes, or distant metastases at detection were defined as "unfavourable." Of 548 BRCA1/2 mutation carriers ≥60 years in 2012, 395 (72%) did not have bilateral mastectomy before the age of 60. Of these 395, 224 (57%) had a history of breast or other invasive carcinoma. In 136 BRCA1/2 mutation carriers, we compared 148 breast cancers (including interval cancers) detected ≥60, of which 84 (57%) were first breast cancers. With biennial mammography 53% (30/57) of carcinomas were detected in unfavourable stage, compared to 21% (12/56) with annual mammography (adjusted odds ratio: 4·07, 95% confidence interval [1.79‐9.28], p = 0.001). With biennial screening 40% of breast cancers were interval cancers, compared to 20% with annual screening (p = 0.016). Results remained significant for BRCA1 and BRCA2 mutation carriers, and first breast cancers separately. Over 70% of 60‐year old BRCA1/2 mutation carriers remain at risk for breast cancer, of which half has prior cancers. When life expectancy is good, continuation of annual breast cancer screening of BRCA1/2 mutation carriers ≥60 is worthwhile.